Pengaruh Green Human Resource Management terhadap Perilaku Hijau Individu dengan Knowledge Management sebagai Variabel Mediasi pada Perusahaan Manufaktur di Batam - Muchsinati, Evi Silvana; Salwa, Helen; Fatyandri, Adineka (Jurnal Samudra Ekonomi dan Bisnis, 2025)
Green human resource management (GHRM) is a strategy to ensure employees continue to support environmental sustainability. This study examines the influence of GHRM on individual green behavior, with knowledge management as a mediator. The study population included 200 employees of PT. Sat Nusa Persada Batam and PT. Jovan Technologies. Data collection was conducted through questionnaires, and data analysis used SEM-PLS. The results indicate that knowledge management effectively mediates the relationship between GHRM and individual green behavior. Companies are advised to strengthen knowledge management practices, such as training and a culture of knowledge sharing, to encourage green behavior. This step is considered not only to improve the company's environmental performance but also to have a positive impact on society and the environment.